Meningkatkan Motivasi Belajar Siswa Melalui Pendekatan Problem Based Learning Pada Materi Pernikahan Dalam Islam Mata Pelajaran Fikih Di Ma Nurul Huda Kelas Xi - Zaman, Muhammad Badru; Noviani, Elsa; Aqmaliyah, Syifa; Wiguna, Wiwi (JURNAL MANAJEMEN PENDIDIKAN, 2025)
INCREASING STUDENT LEARNING MOTIVATION THROUGH A PROBLEM-BASED LEARNING APPROACH ON THE MATERIAL OF MARRIAGE IN ISLAM FIQH SUBJECTS AT MA NURUL HUDA CLASS XIMotivation to learn is an important factor in the success of the learning process. One approach that can be applied to increase student learning motivation is Problem-Based Learning (PBL). This approach focuses on solving real problems that are relevant to students' lives, so that it can encourage their active involvement in learning. This research aims to measure the effectiveness of the PBL method in increasing students' learning motivation on the material Marriage in Islam in the Fiqh subject in class XI MA Nurul Huda. This research uses the classroom action research (PTK) method with a qualitative and quantitative approach. Data was obtained through observation, questionnaires and interviews with students and analyzed descriptively. The research results showed that the application of the PBL method was able to increase students' learning motivation significantly. Students become more active in discussions, more interested in the material being studied, and show a deeper understanding of the concept of marriage in Islam. Based on these findings, it can be concluded that the Problem-Based Learning method is an effective approach in increasing student learning motivation. Therefore, teachers are advised to integrate this method in the learning process to create a more interactive and meaningful learning environment